2002
DOI: 10.1152/ajpendo.00428.2001
|View full text |Cite
|
Sign up to set email alerts
|

New creatine transporter assay and identification of distinct creatine transporter isoforms in muscle

Abstract: . New creatine transporter assay and identification of distinct creatine transporter isoforms in muscle. Am J Physiol Endocrinol Metab 283: E390-E401, 2002. First published February 26, 2002 10.1152/ajpendo.00428.2001.-Despite the pivotal role of creatine (Cr) and phosphocreatine (PCr) in muscle metabolism, relatively little is known about sarcolemmal creatine transport, creatine transporter (CRT) isoforms, and subcellular localization of the CRT proteins. To be able to quantify creatine transport across the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
37
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 71 publications
9
37
0
Order By: Relevance
“…Furthermore, the existence of CRT splice variants has recently been suggested, based on genetics studies using rapid amplification of cDNA ends methods (17). Recent immunofluorescence studies have indicated a high degree of intracellular CRT localization (16), which is consistent with a mainly mitochondrial localization (15). This finding is in contrast to the general view that CRT, represented here by two major ϳ55-and ϳ70-kDa CRT-related proteins, is localized exclusively in the plasma membrane.…”
supporting
confidence: 81%
See 4 more Smart Citations
“…Furthermore, the existence of CRT splice variants has recently been suggested, based on genetics studies using rapid amplification of cDNA ends methods (17). Recent immunofluorescence studies have indicated a high degree of intracellular CRT localization (16), which is consistent with a mainly mitochondrial localization (15). This finding is in contrast to the general view that CRT, represented here by two major ϳ55-and ϳ70-kDa CRT-related proteins, is localized exclusively in the plasma membrane.…”
supporting
confidence: 81%
“…Instead, it was also recently reported that only a minor CRT protein species with an intermediate apparent molecular mass of ϳ58 kDa is located in the plasma membrane (15). This ϳ58-kDa polypeptide has been identified by surface biotinylation of intact cardiomyocytes, followed by Western blotting with anti-CRT antibodies, or alternatively by Western blotting of highly enriched plasma membrane fractions (15). Also in contrast to the prevailing view that mitochondria do not contain Cr, PCr uptake into isolated rat heart mitochondria had been reported earlier (18) and was attributed, however, to the activity of adenine nucleotide translocase.…”
mentioning
confidence: 99%
See 3 more Smart Citations